(untitled) (Management and Connections Journal, 2021)
The objective of this study is to map the use of Construal Level Theory (CLT) in publications in international journals to identify research opportunities. 50 articles from six international databases were selected and submitted to bibliometric and systemic analysis. The results showed that most studies explore only one psychological dimension. The simultaneous use of different psychological dimensions with the same event reveals a research gap. A limited number of studies have investigated organizational events, which characterizes a research opportunity. Also noteworthy is the small collection with the inclusion of this theory in the analysis of topics in the area of ​​administration and accounting. The use of CLT is recent in international studies and presents infinite possibilities of research, mainly in the administration and accounting area. Their exploration contributes to understanding why people interpret the same events differently and their effect on decision making.